Dementia Early-Stage Cognitive Aids New Trial (DESCANT) of memory aids and guidance for people with dementia: randomised controlled trial. Issue 9 (19th October 2021) - Clarkson, Paul; Pitts, Rosa; Islam, Saiful; Peconi, Julie; Russell, Ian; Fegan, Greg; Beresford, Rebecca; Entwistle, Charlotte; Gillan, Vincent; Orrell, Martin; Challis, David; Chester, Helen; et al.
Abstract : Background: Common memory aids for people with dementia at home are recommended. However, rigorous evaluation is lacking, particularly what guidance or support is valued. Objective: To investigate effects of memory aids and guidance by dementia support practitioners (DSPs) for people in early-stage dementia through a pragmatic, randomised controlled trial. Methods: Of 469 people with mild-to-moderate dementia and their informal carers, 468 were randomised to a DSP with memory aids or to usual care plus existing dementia guide. Allocation was stratified by Trust/Health Board; time since first attendance at memory service; gender; age; and living with primary carer or not. Primary outcome was Bristol Activities of Daily Living Scale (BADLS) Score at 3 and 6 months (primary end-point). Secondary outcomes for people with dementia: quality of life (CASP-19; DEMQOL); cognition and functioning (Clinical Dementia Rating Scale; S-MMSE); capability (ICECAP-O); social networks (LSNS-R); and instrumental daily living activities (R-IDDD). Secondary outcomes for carers: psychological health (GHQ-12); sense of competence (SSCQ). Results: DSPs were successfully trained, compliance was good and welcomed by participants. Mean 6 months BADLS Score increased to 14.6 (SD: 10.4) in intervention and 12.6 (SD: 8.1) in comparator, indicative of greater dependence in the activities of daily living. Adjusted between-group difference was 0.38 (95% CI: −0.89 to 1.65, p=0.56). Though this suggests greater dependency in the intervention group the difference was not significant. No differences were found in secondary outcomes. Conclusions: This intervention did not maintain independence in the activities of daily living with no improvement in other outcomes for people with dementia or carers. Trial registration number: Current Controlled Trials ISRCTN12591717 .